2020
DOI: 10.2967/jnumed.120.254656
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of single-time-point dosimetry for radiopharmaceutical therapies

Abstract: Due to challenges in performing routine personalized dosimetry in radiopharmaceutical therapies, interest in single-time-point (STP) dosimetry, particularly utilizing only one SPECT scan, is on the rise.Meanwhile, there are questions about reliability of STP dosimetry, with limited independent validations.In the present work, we analyze two STP dosimetry methods and evaluate dose errors for a number of radiopharmaceuticals based on effective half-life distributions. Method:We first challenged the common assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 19 publications
5
50
0
Order By: Relevance
“…PRRT dosimetry requires at least two imaging time points, as tissue activity curves exhibit a bi-exponential asymmetric bell shape. This feature renders proposed single time-point estimates inaccurate [ 48 ], which is only for a single exponential starting from t = 0, the model used to propose it [ 49 ]. One time point after the maximal uptake is needed, e.g., 24 h post-injection, and another time point somewhere around one effective half-life, i.e., 48 or 72 h post 90 Y injection and 5 to 8 days post 177 Lu injection.…”
Section: Individual Prtt Optimization Planningmentioning
confidence: 99%
“…PRRT dosimetry requires at least two imaging time points, as tissue activity curves exhibit a bi-exponential asymmetric bell shape. This feature renders proposed single time-point estimates inaccurate [ 48 ], which is only for a single exponential starting from t = 0, the model used to propose it [ 49 ]. One time point after the maximal uptake is needed, e.g., 24 h post-injection, and another time point somewhere around one effective half-life, i.e., 48 or 72 h post 90 Y injection and 5 to 8 days post 177 Lu injection.…”
Section: Individual Prtt Optimization Planningmentioning
confidence: 99%
“…This approach is resource intensive and onerous for patients as they must attend for several scans. However, recently it has been shown that, with prior knowledge of the biokinetics of the MRT agent, it is possible to estimate the integrated activity and, therefore, dose from imaging data acquired at a single time point [55]. In a 2021 study by Hou et al [55], the optimal SPECT imaging time point was determined to be 72 and 48 h after administration of [ 177 Lu]Lu-DOTATATE and [ 177 Lu]Lu-PSMA, respectively.…”
Section: Advances In Molecular Radiotherapy Dosimetry Facilitate Combination With External Beam Radiotherapymentioning
confidence: 99%
“…However, recently it has been shown that, with prior knowledge of the biokinetics of the MRT agent, it is possible to estimate the integrated activity and, therefore, dose from imaging data acquired at a single time point [55]. In a 2021 study by Hou et al [55], the optimal SPECT imaging time point was determined to be 72 and 48 h after administration of [ 177 Lu]Lu-DOTATATE and [ 177 Lu]Lu-PSMA, respectively. In a 2018 study reported by H€ anscheid et al [56], a single time point quantitative activity measurement on SPECT/CT at 96 h post-administration of [ 177 Lu] Lu-DOTA-TATE or [ 177 Lu]Lu-DOTA-TOC could be used to estimate absorbed doses.…”
Section: Advances In Molecular Radiotherapy Dosimetry Facilitate Combination With External Beam Radiotherapymentioning
confidence: 99%
“…PRRT dosimetry requires at least two imaging time-points, as tissue activity curves exhibit a bi-exponential asymmetric bell shape. This feature makes inaccurate proposed single time-point estimates [48], which is only for a single exponential starting from t = 0, the model used to propose it [49]. One time point after the maximal uptake is needed, e.g., 24h post injection, and another time-point somewhere around one effective half-life, i.e., 48 or 72h post 90 Y injection and 5 to 8 days post 177 Lu injection.…”
Section: Individual Prtt Optimization Planningmentioning
confidence: 99%